Anti-KIT DNA aptamer-conjugated porous silicon nanoparticles for the targeted detection of gastrointestinal stromal tumors. Issue 47 (23rd November 2022) - Vijayakumar, Sanahan; Nasr, Seyedmehdi H.; Davis, Jacob E.; Wang, Edward; Zuidema, Jonathan M.; Lu, Yi-Sheng; Lo, Yu-Hwa; Sicklick, Jason K.; Sailor, Michael J.; Ray, Partha
Abstract : A preclinical mouse model for in vivo imaging of Gastrointestinal Stromal Tumors (GIST) using KIT-aptamer targeted fluorescently-labeled porous silicon nanoparticles. Abstract : Evaluation of Gastrointestinal Stromal Tumors (GIST) during initial clinical staging, surgical intervention, and postoperative management can be challenging. Current imaging modalities ( e.g., PET and CT scans) lack sensitivity and specificity. Therefore, advanced clinical imaging modalities that can provide clinically relevant images with high resolution would improve diagnosis. KIT is a tyrosine kinase receptor overexpressed on GIST. Here, the application of a specific DNA aptamer targeting KIT, decorated onto a fluorescently labeled porous silicon nanoparticle (pSiNP), is used for the in vitro & in vivo imaging of GIST. This nanoparticle platform provides high-fidelity GIST imaging with minimal cellular toxicity. An in vitro analysis shows greater than 15-fold specific KIT protein targeting compared to the free KIT aptamer, while in vivo analyses of GIST-burdened mice that had been injected intravenously (IV) with aptamer-conjugated pSiNPs show extensive nanoparticle-to-tumor signal co-localization (>90% co-localization) compared to control particles. This provides an effective platform for which aptamer-conjugated pSiNP constructs can be used for the imaging of KIT-expressing cancers or for the targeted delivery of therapeutics.